Label-free chronopotentiometric glycoprofiling of prostate specific antigen using sialic acid recognizing lectins - Belicky, Stefan; Černocká, Hana; Bertok, Tomas; Holazova, Alena; Réblová, Kamila; Paleček, Emil; Tkac, Jan; Ostatná, Veronika (Bioelectrochemistry (Amsterdam, Netherlands), 2017)
In recent decades, it has become clear that most of human proteins are glycosylated and that protein glycosylation plays an important role in health and diseases. At present, simple, fast and inexpensive methods are sought for clinical applications and particularly for improved diagnostics of various diseases, including cancer. We propose a label- and reagent-free electrochemical method based on chronopotentiometric stripping (CPS) analysis and a hanging mercury drop electrode for the detection of interaction of sialylated protein biomarker a prostate specific antigen (PSA) with two important lectins: Sambucus nigra agglutinin (SNA) and Maackia amurensis agglutinin (MAA). Incubation of PSA-modified electrode with specific SNA lectin resulted in an increase of CPS peak H of the complex as compared to this peak of individual PSA. By adjusting polarization current and temperature, PSA-MAA interaction can be either eliminated or distinguished from the more abundant PSA-SNA complex. CPS data were in a good agreement with the data obtained by complementary methods, namely surface plasmon resonance and fluorescent lectin microarray. It can be anticipated that CPS will find application in glycomics and proteomics.
Keywords: Maackia; Sambucus nigra; Chronopotentiometric analysis; A prostate specific antigen; Electrochemistry; bez černý; kyselina N-acetylneuraminová; Prostate-Specific Antigen; N-Acetylneuraminic Acid; aglutininy; Sialylated glycan isomers; elektrochemie; Agglutinins; Lectin-glycoprotein interaction; prostatický specifický antigen; elektrická vodivost; Mercury electrode; Electric Conductivity